Improving Efficiency in the Precast Plate Installation Process - สาพิมพ์, เกศกนก; พิมภาภรณ์, ณัฐชฎา; ชีชนะ, ปิยะนาถ; โข่จา, อานนท์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to find the cause of the efficiency problem in the PRECAST installation process and to improve the efficiency in the PRECAST installation process. The research was conducted using quality control tools, collecting data on defects before and after the improvement with a checklist, selecting problems that need to be improved with a Pareto chart, and analyzing the cause of the problem to lead to problem solving with a cause-and-effect diagram. The production process flow chart was used in conjunction with the 7 principles of waste reduction and the ECRS principle to apply to improve the process. The results of the research can be summarized as follows: The study of the cause of time loss in the PRECAST installation work, the researcher found that the cause of time loss in the installation work There are 3 causes of time wasted in installation work: the complicated work process, which is 10.36 percent, wasted time in installation work, 7.00 percent, and wasted time in other sub-tasks, 2.4 percent. The results of the work process efficiency test found that the work process before the improvement had a total of 13 activities, after the improvement, there were 10 activities, reduced by 2 activities. Before the improvement, the total travel distance was 87 meters, after the improvement, there were 62 meters, reduced by 25 meters. Before the improvement, the total work time was 4 hours, after the improvement, there were 1 hour and 55 minutes, reduced by 2 hours and 45 minutes.